Molecular characterization and antimicrobial susceptibility profiles in Streptococcus agalactiae colonizing strains: association of erythromycin resistance with subtype III-1 genetic clone family - Florindo, C. (2011)
Knowledge of the epidemiology of Streptococcus agalactiae in Portugal is limited: therefore, the present study aimed to investigate the carriage rate of S. agalactiae among Portuguese women of reproductive age and the prevalence of antibiotic resistance, as well as to perform a molecular characterization of the clinical isolates. S. agalactiae was recovered from 6.2% of 4269 women during the period 2005–2007, with a predominance of capsular genotypes III (35%), V (33%), Ia (16%) and II (10%) in a sample of 100 isolates. To our knowledge, this is the first report of the S. agalactiae colonization rate in Portugal determined according to CDC guidelines. All isolates were susceptible to penicillin and vancomycin, whereas resistance to clindamycin and erythromycin was detected in 10% and 19% of isolates, respectively. Among the 19 erythromycin-resistant isolates, ten (53%) displayed the constitutive MLSB phenotype (conferring high-level resistance to macrolides), eight (42%) had the inducible MLSB, and the M phenotype accounted for one isolate (5%). erm methylase genes were exclusively associated with MLSB phenotype isolates, whereas the M phenotype was a result of the presence of mefA. Multilocus sequence typing analysis of the genetic relatedness among isolates presenting resistance to erythromycin demonstrated a novel association between erythromycin resistance and the subtype III-1/ST-19 genetic clone family.